A review for the clinician: classifications, genetics, and treatment for neuroendocrine neoplasms of the thymus (thymic carcinoids) - Lang, Matthias; Anamaterou, Chrysanthi; Mohr, Isabelle; Černá, Mária; Röhrich, Manuel; Tjaden, Christine (Neuroendocrinology, 2025)
Background: Thymic carcinoids or neuroendocrine neoplasms (t-NEN) are a rare entity with a dismal prognosis. About 25% of the tumors are related to multiple endocrine neoplasia type I (MEN-1), where they contribute significantly to mortality. The tumors are classified according to the WHO classification, TNM classification and Masaoka-Koga staging system, although none of the classifications have been developed for t-NEN. A recently proposed t-NEN specific morphomolecular classification is based on copy number instability scores. Its role is yet to be defined. The prognosis depends on resectability, histological features, metastasis, the amount of copy number instabilities and mitotic activity. Summary: No study-based therapies exist. The mainstay of therapy is surgical resection as it is associated with significantly improved long-term survival. Based on published cases and small series, for non-resectable and recurring disease, platinum-based chemotherapies are preferred in neuroendocrine carcinoma, while everolimus and temozolomide are recommended in thymic neuroendocrine tumors. Key Messages: This review covers current classification systems and the knowledge of genetic disorders and medical therapies.
Veröffentlicht: 11. März 2025
Gesehen am 10.02.2026